2008
DOI: 10.1159/000137699
|View full text |Cite
|
Sign up to set email alerts
|

Drug-Eluting Stents Compared with Bare Metal Stents Improve Late Outcome after Saphenous Vein Graft but Not after Large Native Vessel Interventions

Abstract: Objectives: To define long-term efficacy of different stent types in saphenous vein graft (SVG) interventions. Methods: In BASKET (Basel Stent Cost Effectiveness Trial), major adverse cardiac events (MACE), i.e. cardiac death, myocardial infarction and symptom-driven target vessel revascularization (TVR) were assessed after 18 months comparing drug-eluting stents (DES) versus bare metal stents (BMS), and SVG and large native vessels (≧3.0 mm). Results: Large vessel interventions were performed in 605 patients.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(34 citation statements)
references
References 65 publications
(47 reference statements)
3
31
0
Order By: Relevance
“…There were two randomized trials [10,11], one subgroup analysis from a randomized trial [12] and 26 observational studies comparing DES with BMS for SVG lesions that met selection criteria for our metaanalysis. A total of 7,994 patients were included in this meta-analysis with 4,187 patients in the DES arm and 3,807 patients in the BMS group (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There were two randomized trials [10,11], one subgroup analysis from a randomized trial [12] and 26 observational studies comparing DES with BMS for SVG lesions that met selection criteria for our metaanalysis. A total of 7,994 patients were included in this meta-analysis with 4,187 patients in the DES arm and 3,807 patients in the BMS group (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Randomized controlled trials (RCTs) have yielded divergent results in terms of the safety and efficacy of DES vs. BMS for PCI of SVG lesions [10,12]. Infact, results from the DELAYED RRISC trial demonstrated an increased risk of death with the use of sirolimus eluting stents (SES), cautioning the interventional cardiology community regarding the use of DES in SVG lesions [10].…”
Section: Introductionmentioning
confidence: 99%
“…Two prospective, randomized, single-center studies have reported comparisons of DES and BMS in SVG lesions. In a post hoc subgroup analysis of the BASKET (Basel Stent Kosten Effektivitats Trial) study, the subgroup of 47 patients who underwent SVG PCI derived greater benefit from DES implantation during a follow-up of 18 months (24). In the BASKET study, major adverse cardiac events occurred in 62% in the BMS group versus 21% in the DES group (p ϭ 0.007), mainly due to a lower TVR rate in the DES group (46% vs. 18%, p ϭ 0.04).…”
Section: Discussionmentioning
confidence: 99%
“…26,33 One study abstract was found after reviewing major meetings' programs. 35 Finally, 25 studies (22 observational, 14 -33,35,36 2 randomized, controlled trials, 12,13 and 1 secondary subgroup analysis of a randomized, controlled trial 37 ) were included in this study-level meta-analysis (Figure 1). The main characteristics of the 25 studies are shown in Table 1.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
“…Periprocedural treatment with clopidogrel was more disparate among eligible studies. In most trials, clopidogrel was prescribed for at least 1 month after BMS placement 13,[17][18][19][21][22][23]25,[27][28][29]36 and for at least 3 18 -20,22,25,28 or 6 months 13,14,17,19,21,23,25,27,28,32,33,36,37 after DES implantation. In the DELAYED RISCC study, 12 clopidogrel was administered for at least 2 months in all patients.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%